Simultaneous suppression of PKM2 and PHGDH elicits synergistic anti-cancer effect in NSCLC - Wang, Kaixuan; Lu, Hao; Wang, Xinmiao; Liu, Qingxia; Hu, Jinxia; Liu, Yao; Jin, Meihua; Kong, Dexin (Frontiers in Pharmacology, 2023)
Metabolic reprogramming is a hallmark of human cancer. Cancer cells exhibit enhanced glycolysis, which allows glycolytic intermediates to be diverted into several other biosynthetic pathways, such as serine synthesis. Here, we explored the anti-cancer effects of the pyruvate kinase (PK) M2 inhibitor PKM2-IN-1 alone or in combination with the phosphoglycerate dehydrogenase (PHGDH) inhibitor NCT-503 in human NSCLC A549 cells in vitro and in vivo. PKM2-IN-1 inhibited proliferation and induced cell cycle arrest and apoptosis, with increased glycolytic intermediate 3-phosphoglycerate (3-PG) level and PHGDH expression. The combination of PKM2-IN-1 and NCT-503 further suppressed cancer cell proliferation and induced G2/M phase arrest, accompanied by the reduction of ATP, activation of AMPK and inhibition of its downstream mTOR and p70S6K, up-regulation of p53 and p21, as well as down-regulation of cyclin B1 and cdc2. In addition, combined treatment triggered ROS-dependent apoptosis by affecting the intrinsic Bcl-2/caspase-3/PARP pathway. Moreover, the combination suppressed glucose transporter type 1 (GLUT1) expression. In vivo, co-administration of PKM2-IN-1 and NCT-503 significantly inhibited A549 tumor growth. Taken together, PKM2-IN-1 in combination with NCT-503 exhibited remarkable anti-cancer effects through induction of G2/M cell cycle arrest and apoptosis, in which the metabolic stress induced ATP reduction and ROS augmented DNA damage might be involved. These results suggest that the combination of PKM2-IN-1 and NCT-503 might be a potential strategy for the therapy of lung cancer.